Pancreatic insufficiency following abdominal irradiation. Issue 661 (November 1980) - Kingham, J. G.; Barrett, A.
Abstract : A case is reported of pancreatic insufficiency following abdominal irradiation for Hodgkin's disease in a man aged 47 years. The effects of radiation on the pancreas are discussed. It is suggested that post irradiation steatorrhoea may have a pancreatic as well as an enteric cause.